Youth and Sport in Montenegro - Miomir Maros (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
In this paper we investigate to which measure sport is developed among young people in Montenegro and what should be done to improve and spread physical culture among young people and beyond school systems in order to infl uence their proper development and to create opportunities for choosing potential talents for certain sports disciplines, who would later grow into top athletes and members of national teams. In addition to the theoretical framework set out from referent literature on sports, we will analyze the indicators - the existing regulation and strategy, and analyze the structured interviews conducted among sports professionals, based on which we will form the theory and sublimate the conclusions of work, as recommendations for improving sports among young people. Disadvantages are inadequate realization of teaching in schools, lack of adequate infrastructure in schools, lack of athletic stadium in the capital of Montenegro and lack of sports schools beyond classes. Advantages are great sports potential in youth, youth interest in sport and generations of educated professors in physical culture. The recommendations are related to addressing the shortcomings that exist and the adoption of laws that will stimulate the development of sports among young people.